La convergence absolue de la série d’interpolation - Nasekovskaja, N. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. С. Насековская. Абсолютная сходимость интерполяционного ряда N. Nasekovskaja. Interpoliacinės eilutės absoliuti konvergencija